(untitled) (Third Sector Social Economic Review, 2024)
This study aims to examine the perceptions of university students towards individuals with disabilities and their cognitive and affective empathy levels. In this context, students who are actively studying at Kırıkkale University were included in the study. This study was carried out using descriptive method in accordance with the quantitative research model. In the study, socio-demographic information form, Perception Scale for Individuals with Disabilities and Cognitive and Affective Empathy Scale were used to obtain data on the individual characteristics of the participants. Cluster sampling method, one of the probability sampling methods, was used to determine the sample. For this purpose, the study sample consisted of 970 students from five faculties, based on the voluntary participation of the students studying at the Faculty of Law, Faculty of Veterinary Medicine, Faculty of Humanities and Social Sciences, Faculty of Health Sciences and Faculty of Fine Arts, stratified according to the placement score types in the fall semester of the 2023-2024 academic year. According to the results obtained, there was a significant difference between the perceptions of disabled people and affective empathy levels of the students participating in the study and their gender and faculty of study, while a significant difference was also found between the perceptions of disabled people and income level (p<0.0.5). When the relationship between the total scores of the two scales was analysed, a negative and low level relationship was found between Perception of People with Disabilities and Cognitive and Affective Empathy.